Research progress on symptom clusters of patients with gastric cancer (胃癌患者症状群的研究进展) - SHI Linlin (石琳琳); CHAI Shouxia (柴守霞); ZHU Yalin (朱雅麟); DAI Cui (戴翠); TANG Jing (汤婧) (中西医结合护理)
In this paper, the category composition, evaluation tools, influencing factors and intervention methods of symptom clusters of patients with gastric cancer were reviewed, and the problems existing in the existing research were summarized, in order to provide reference for clinical practice and nursing research. (本文从胃癌患者症状群的类别构成、评价工具、影响因素及干预方法进行综述, 并对现有研究中存在的问题进行总结, 以期为临床实践及护理研究提供参考。)